Peran Kepribadian Proaktif dan Resiliensi terhadap Keterikatan Kerja Petugas Pemadam Kebakaran dan Penyelamatan - Aufa Rusydina Husna; Aulia Aulia (Jurnal Ilmu Perilaku, 2023)
Work engagement is an important aspect, especially for employees who have a job with a high level of risk, to minimize the impact of risks and maximize their performance. Therefore, this research investigated the role of proactive personality and resilience in work engagement. The method was a quantitative approach with a correlational research design. The population in this study were firefighters and rescue personnel in Yogyakarta. The sampling technique used was saturation sampling with a sample size of 167 individuals. Data were collected using the Modified UWES by Aulia et al. (2019), the Modified PPS by the author, and the Resilience Scale by Aulia et al. (2022). The analytical technique used was multiple linear regression. The study's results indicate that proactive personality and resilience played a highly significant role in work engagement. A proactive personality significantly and positively influences work engagement, as does resilience. Both proactive personality and resilience contributed effectively to work engagement by 61.2%, whereas the remaining 38.8% was determined by other factors not discussed in this study. This finding can be used by organizations and companies to understand their employees related to work attachment to increase human resources within the scope of work.